Qualitative determination of arecoline in Areca catechu - Torres, Neonita D.
Areca catechu was assayed fro total alkaloids calculated as arecoline, adn was found to contain 0.51%. Arecoline was qualitatively determined with the use of two methods of isolation. Color and precipitation reactions were performed on the isolated substance. And of the three batches of isolated substances, only two gave a highly comparable result, with respect to color and precipitation reactions. The isolated substances were also chromatographed using silica gel and a number of solvent systems.